Osteoblastogenesis of adipose-derived mesenchymal stem cells in chronic kidney disease patient with regular hemodialysis. (December 2022) - Tjempakasari, Artaria; Suroto, Heri; Santoso, Djoko
Abstract: Background: Chronic kidney disease (CKD) is a health problem associated with high morbidity and mortality. Mineral and bone disorders are complications of CKD with a risk of fractures and cardiovascular disease. Mesenchymal stem cells can differentiate into osteoblasts and regulate their regulation by a network of cytokines and transcription factors. Objective: Analyzing differences in osteoblastogenesis of adipose mesenchymal stem cells in CKD patients and healthy people. Methods: The study sample was adipose mesenchymal stem cells from CKD patient undergoing hemodialysis and healthy people. Osteoblastogenesis was assessed by measuring the concentrations of transforming growth factor-β1 (TGF-β1), bone morphogenetic protein-2 (BMP-2), and (DKK-1) in culture media. The Elisa method measured the concentration of these parameters on days 4, 7, 14, and 21. Data were analyzed using an independent t -test and post hoc test with p -value <0.05. Result: There was a significant difference in CKD patients with increasing TGF-β1 on day 4 ( t  = 2.821; 95% CI = 30, 498–199, 727; p  = 0.010) and decreased on day 14. In the BMP-2 parameter, there was an increase on day 7 ( t  = 4.291; 95% CI = 0.289–0.831; p  <0.001). Similar conditions were also found in the DKK-1 parameter, increasing on the 7th day, but there was no significant difference ( p  = 0.583). Conclusion: Osteoblastogenesis in adipose mesenchymal stem cells in CKD patients differs from that in healthy individuals. Osteoblasts fail in maturation and cause failure in matrix mineralization. Highlights: Increased TGF-β1 levels in CKD patients occurs on day 4 and 7. Increased BMP-2 levels in CKD patients occurs on day 7. On the seventh day, increased DKK-1 levels in CKD patients or/and healthy people.